Electrochemical micro- and nanostructuring by cathodic deposition on solid electrolytes - Peppler, Klaus; Justus Liebig University Giessen (My University, 2009)
This work deals with the influence of experimental parameters on the cathodic deposition of silver on solid silver cation conductors. In order to investigate the cathodic deposition on solid electrolytes for electrochemical micro- and nanostructuring it is necessary to employ a relative simple model system. Hence, in this work the transference cell (-)Ag|AgBr(single crystal)|Ag(+) in different configurations was used. The above mentioned single crystalline silver bromide as solid electrolyte has several advantages. It is stable at ambient conditions, even to irradiation with light. It exhibits only a marginal electronic conductivity, hence it is almost a pure silver cation conductor. Thus, electronic current is converted fully into a cation current at the Ag|AgBr interface. The transference cell of the type (-)Ag|Ag2S(polycrystalline)|Ag(+) was used for a special kind of electrolyte preparation, i.e. the embedding into a porous template material. Silver sulfide has the advantage of a relative easy fabrication which is favorable for filling pores of a template. But it is a mixed ionic and electronic conductor with a considerable deviation from stoichiometry. In equilibrium with silver (which is the case when in contact with a silver electrode at elevated temperatures) the transference number for electrons exceeds the transference number for silver cations considerably. Thus, electronic current is not converted fully into a cationic current at the Ag|Ag2S interface.The present work is divided into three parts:In chapter 2.1 the cathodic deposition of silver at microelectrodes on single crystalline silver bromide was dealt with. Depositions were carried out galvanostatically in order to get constant deposition rates of silver. Two different morphologies of the silver deposits were observed. At low current densities (j < 0.1 A/cm; I < 0.5 A, d(Ag-microelectrode) = 25 µm) growth in height (perpendicular to the electrolyte surface) in form of whiskers was observed. In this case the flexible microelectrodes were pushed up by the growing whiskers. At high current densities (j > 0.6 A/cm; I > 3.0 A, d(Ag-microelectrode) = 25 µm) growth parallel to the electrolyte surface in form of dendrites was observed. Variation of temperature caused a considerable change in morphology. The diameters of whiskers decreased from a few micrometers to several hundreds of nanometers at a decrease of temperature from 300 °C to 150 °C. Dendrites changed from an isotropic form to an anisotropic morphology with preferential growth in two directions (presumably along designated crystallographic directions of the electrolyte). These anisotropic dendrites consisted of whiskers connected to each other. This temperature dependence of morphology could be related to the nucleation rate.In chapter 2.2 the stability of as-deposited electronically isolated metal particles in external electric fields was treated. In the last years the application of solid state ionics in future memory devices has been investigated, e.g. the switching between two resistive states by cathodic metal deposition and subsequent dissolution. Thus, the stability of as-deposited metal is an issue which has to be considered. It could be shown that electronically (but not ionically) isolated silver metal particles on a solid silver cation conductor behaved as bipolar electrodes when put in an external electric field. They were dissolved at the anodic side, and silver was deposited at their cathodic side. The deposition occurred neither in form of whiskers nor dendrites, but as a thin film. This is a new kind of deposition morphology for silver on solid silver electrolytes.In chapter 2.3 the deposition of silver in the form of wires with predefined diameters was reported. The cathodic deposition of silver on silver bromide at microelectrodes yielded whiskers with different diameters, depending on experimental conditions. But in this case the diameter could not be predicted prior to the experiment. In order to obtain silver microwires (i.e. whiskers) with predefined diameters it was necessary to embed the electrolyte in a porous template with straight cylindrical pores. As templates porous silicon and porous alumina were used. The pores were filled with silver sulfide by a simple chemical reaction of silver and sulfur. Subsequent electrodeposition led to silver wires with the same diameter as the pores of the template.Finally, this work was concluded by a classification (chapter 3.1) and an outlook (chapter 3.2).

In der vorliegenden Arbeit wurde der Einfluss experimenteller Parameter (Temperatur, Stromdichte, Kathodengeometrie, Elektrolytgeometrie) auf die kathodische Abscheidung von Ag auf festen Ag-Elektrolyten untersucht. Hierzu wurden zwei Überführungszellen (-)Ag|AgBr(Einkristall)|Ag(+) und (-)Ag|Ag2S(polykristallin)|Ag(+) in verschiedenen Konfigurationen verwendet. Bei diesen Zellen handelt es sich um relativ einfache Modellsysteme. Die Verwendung von einkristallinem AgBr hat mehrere Vorteile: Zum einen ist es stabil unter Laborbedingungen, auch einige Zeit gegen die Einwirkung von Licht. Zum anderen ist seine elektronische Leitfähigkeit vernachlässigbar klein, d.h. es ist bei höheren Temperaturen nahezu ein reiner Kationenleiter. Somit wird ein elektronischer Strom an der Ag|AgBr-Grenzfläche (fast) vollständig in einen Ag-Ionenstrom umgewandelt. Die Überführungszelle (-)Ag|Ag2S(polykristallin)|Ag(+) wurde verwendet, um den Elektrolyten in ein Templat einzubringen. Silbersulfid hat den Vorteil, dass es relativ einfach herzustellen ist, somit ist ein Befüllen von Poren ohne großen Aufwand möglich. Es hat jedoch den Nachteil, dass es ein gemischter Leiter mit elektronischer und ionischer Leitfähigkeit ist. Im Gleichgewicht mit Ag (was in einer Zelle mit Ag-Elektroden bei höheren Temperaturen gegeben ist) ist die Überführungszahl für Elektronen wesentlich größer als die für Ag-Ionen. Deshalb wird an der Phasengrenze Ag|Ag2S nur ein kleiner Teil des elektrischen Stroms in einen Ag-Ionenstrom überführt.Im Wesentlichen ist diese Arbeit aus drei Teilen zusammengesetzt:In Kapitel 2.1 wird die Abscheidung von Ag an Mikroelektroden auf festem AgBr abgehandelt. Um eine konstante Abscheidungsrate von Ag zu gewährleisten, wurden die Experimente unter galvanostatischen Bedingungen durchgeführt. Es konnten zwei Morphologien beobachtet werden: Bei niedrigen Stromdichten (j < 0,1 A/cm; I < 0,5 A, d(Ag-Mikroelektrode) = 25 µm) wurde ein Wachstum in die Höhe (senkrecht zur Elektrolytoberfläche) in Form von Ag-Whiskern beobachtet. Die Mikroelektroden aus flexiblen Ag-Drähten wurden dabei von den wachsenden Whiskern nach oben weggedrückt. Bei hohen Stromdichten (j > 0,6 A/cm; I > 3,0 A, d(Ag-Mikroelektrode) = 25 µm) wurde ein Wachstum parallel zur Oberfläche in Form von Dendriten beobachtet. Eine Änderung der Temperatur hatte eine beachtliche Änderung der Morphologie zur Folge. Der Durchmesser der Whisker nahm bei einer Temperaturerniedrigung von 300 °C zu 150 °C von wenigen Mikrometern auf einige Hundert Nanometer ab. Im Fall der Dendriten wurde eine Änderung von isotropem zu anisotropem Wachstum bevorzugt in zwei Raumrichtungen (vermutlich entlang ausgewiesener kristallographischer Ausrichtungen des Elektrolyten) beobachtet. Diese Temperaturabhängigkeit kann mit der Nukleationsrate in Zusammenhang gebracht werden.In Kapitel 2.2 wird über die Stabilität von elektronisch (aber nicht ionisch) isolierten Metallpartikeln, die sich in einem externen elektrischen Feld befinden, berichtet. In den letzten Jahren wurden neue Ansätze für zukünftige Speichermedien basierend auf Konzepten der Festkörperelektrochemie verfolgt. So wurde z.B. das Hin- und Herschalten zwischen zwei Zuständen mit unterschiedlich hohen Widerständen durch das Abscheiden und Auflösen von Metallen in oder auf Festelektrolyten untersucht. Hierbei spielt also die Stabilität des abgeschiedenen Metalls eine wichtige Rolle für die Erhaltung der gespeicherten Daten. Es konnte gezeigt werden, dass sich elektronisch isolierte Ag-Partikel auf einem festen Ag-Ionenleiter wie bipolare Elektroden verhielten, wenn ein externes elektrisches Feld angelegt wird. Folglich wurden sie an ihrer anodischen Seite aufgelöst, und an ihrer kathodischen Seite wurde Ag abgeschieden. Die Abscheidung erfolgte dabei in keiner der bisher beobachteten Morphologien, sondern in Form von dünnen Ag-Filmen, also weder in Form von Whiskern noch Dendriten.In Kapitel 2.3 wird über die Abscheidung von Ag in Form von Ag-Drähten mit vorgegebenem Durchmesser berichtet. Wie schon berichtet erhält man bei der Abscheidung von Ag an Mikroelektroden auf AgBr Whisker mit unterschiedlichen Durchmessern in Abhängigkeit der experimentellen Parameter. Allerdings konnte im Vorfeld nicht vorhergesagt werden, welchen Durchmesser die Whisker haben werden. Um Ag-Mikrodrähte mit vorgegebenen Durchmessern zu erhalten, ist es deshalb nötig, den Elektrolyten in ein Templat mit geraden zylindrischen Poren einzubetten. Dadurch wird die Abscheidung von Ag räumlich begrenzt und die Ag-Drähte haben den gleichen Durchmesser wie die Poren. Als Template wurden poröses Aluminiumoxid und poröses Silizium verwendet. Die Poren wurden durch eine einfache chemische Reaktion zwischen Ag und Schwefel gefüllt.Abgeschlossen wird diese Arbeit mit einer Einordnung der eigenen Ergebnisse (Kapitel 3.1) und einem Ausblick (Kapitel 3.2).
Elektrochemische Mikro- und Nanostrukturierung mittels kathodischer Abscheidung auf Festkörperelektrolyten
Keywords: Festkörperelektrolyt; kathodische Metallabscheidung; Whisker; Dendrit; morphologische Instabilität; solid electrolyte; cathodic metal deposition; whisker; dendrite; morphological instabillity; ddc:540